2020
DOI: 10.1016/j.jvs.2019.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Women undergoing endovascular thoracoabdominal aortic aneurysm repair differ significantly from their male counterparts preoperatively and postoperatively

Abstract: Objective: A rational approach to the management of aortic aneurysm disease relies on weighing the risk of aneurysm rupture against the complications and durability of operative repair. In men, seminal studies of infrarenal aortic aneurysm disease and its endovascular management can provide a reasoned argument for the timing and modality of surgery, which is then extrapolated to the management of thoracoabdominal aortic aneurysms (TAAAs). In contrast, there is less appreciation for the natural history of TAAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The lower early mortality is possible with suitable anatomy, team experience, and device improvements over time. [13,16] Complicated aortic or vessel anatomy, worse baseline health and more symptomatic aneurysms may be possible reasons. In our study, symptomatic patients were numerically higher in female group than the male group (52.2% vs. 41.3%, respectively); however, there were no significant differences in the baseline demographics.…”
Section: Discussionmentioning
confidence: 99%
“…The lower early mortality is possible with suitable anatomy, team experience, and device improvements over time. [13,16] Complicated aortic or vessel anatomy, worse baseline health and more symptomatic aneurysms may be possible reasons. In our study, symptomatic patients were numerically higher in female group than the male group (52.2% vs. 41.3%, respectively); however, there were no significant differences in the baseline demographics.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Analyzing 959 patients (163 women), Rieß et al 21 found female patients to be at higher risk of in-hospital mortality (OR 3.21, p<0.001), to have lower long-term survival (hazard ratio 1.51, p=0.006), and to be associated with more complications, including acute renal failure [relative risk (RR) 1.71, 95% CI 1.06 to 2.77], paraplegia (RR 2.71, 95% CI 1.28 to 5.77), and bleeding requiring transfusion (RR 1.76, 95% CI 1.39 to 2.22). Withefort et al 20 also found women to have a higher proportion of Crawford extent I, II, and III aneurysms and higher perioperative mortality (16% vs 6%), with similar survival at 3 years. In contrast to earlier studies, they also demonstrated that women tend to have a more favorable response to endovascular aneurysm exclusion, with satisfying durability and greater aneurysm sac regression compared with a matched cohort of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 A recent systematic review assessed the anatomical feasibility of commercially available AAA stent-grafts, demonstrating that they are primarily designed for the male anatomy. 19 Two recent studies compared sex differences in thoracoabdominal aortic aneurysm (TAAA) patients treated by means of fenestrated/branched endovascular aortic repair (f/bEVAR), 20,21 but no research has yet investigated the sex differences in potential TAAA treatment with off-the-shelf stent-grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Female sex in the American College of Surgeons National Surgical Quality Improvement Program (1,010 open repair -30.7% females and 1,260 EVARs -21.4% females) is associated with higher perioperative mortality and more major complications than for male pts after complex EVAR (juxtarenal, pararenal, or suprarenal) but not after complex open repair [140]. Also, women have a persistent elevated perioperative mortality in women (16%) undergoing endovascular thoracoabdominal aortic aneurysm (TAAA) repair compared with matched men (6%) due to differences in comorbidities, aneurysm extent, and aneurysm size [141]. Worse in-hospital and long-term survival compared to males may also relate to the impact of anatomy on outcome disparities [142].…”
Section: Gender Differences In Aortoiliac Repairmentioning
confidence: 99%